In The Blood: Connecting Variant to Function In Human Hematopoiesis - Nandakumar, Satish K. (Trends Genet, 2020)
Genome-wide association studies (GWAS) have identified thousands of genetic variants associated with a range of human diseases and traits. However, understanding the mechanisms by which these genetic variants impact associated diseases and traits, often referred to as the variant to function (V2F) problem, remains a significant hurdle. Solving the V2F challenge requires us to identify causative genetic variants, relevant cell types/ states, target genes, and mechanisms by which variants can cause diseases or alter phenotypic traits. In this review, we discuss the emerging functional approaches being applied to tackle the V2F problem for blood cell traits, illuminating how human genetic variation can impact key mechanisms in hematopoiesis, as well as highlighting future prospects for this nascent field.